Impact of COVID-19 Pandemic on Dental Education: Experience Sharing from a Malaysian Public University - Faizah Abdul Fatah; Nor Azura Ahmad Tarmidzi; Rohazila Mohamad Hanafiah; Diana Md Zahid; Wan Nor Syariza Wan Ali; Zurairah Ibrahim; Nor Haliza Mat-Baharin,; Nusima Mohamed (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 01-2021) [April 2021]